2008
DOI: 10.1111/j.1574-6968.2008.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a novel α-galactosidase fromBifidobacterium breve203 capable of synthesizing Gal-α-1,4 linkage

Abstract: A novel alpha-galactosidase gene (aga2) was cloned from Bifidobacterium breve 203. It contained an ORF of 2226-bp nucleotides encoding 741 amino acids with a calculated molecular mass of 81.5 kDa. The recombinant enzyme Aga2 was heterogeneously expressed, purified and characterized. Regarding substrate specificity for hydrolysis, Aga2 was highly active towards p-nitrophenyl-alpha-d-galactopyranoside (pNPG). The Km value for pNPG was estimated to be 0.27 mM and for melibiose it was estimated to be 4.3 mM. Aga2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…Bifi dobacterium adolescentis DSM 20083 strain secreted α-galactosidase extracellularly; that was suggested to be a tetrametric structure of the protein [32]. Later, two groups -Goulas et al [33] as well as Zhao et al [34] -reported cloning, expression and characterisation of α-galactosidase from B. bifi dum NCBIM B41171 and B. breve 203, respectively, and it had been found a monomeric nature of this galactosidase with molecular mass about 80 kDa. Tochikura et al [35] however, found that bifi dobacteria exhibit higher hydrolyzing activity toward various p-nitrophenyl glycosides than other intestinal bacteria.…”
Section: Growth Volumetric Productivity and α-Galactosidase Activitymentioning
confidence: 99%
“…Bifi dobacterium adolescentis DSM 20083 strain secreted α-galactosidase extracellularly; that was suggested to be a tetrametric structure of the protein [32]. Later, two groups -Goulas et al [33] as well as Zhao et al [34] -reported cloning, expression and characterisation of α-galactosidase from B. bifi dum NCBIM B41171 and B. breve 203, respectively, and it had been found a monomeric nature of this galactosidase with molecular mass about 80 kDa. Tochikura et al [35] however, found that bifi dobacteria exhibit higher hydrolyzing activity toward various p-nitrophenyl glycosides than other intestinal bacteria.…”
Section: Growth Volumetric Productivity and α-Galactosidase Activitymentioning
confidence: 99%
“…In spite of this, a-galactosidases, capable of catalyzing hydrolysis as well as transglycosylation of a-galacto-oligosaccharides, have only been studied in four bifidobacterial species, i.e. B. adolescentis [62,146], B. bifidum [38], B. breve [167] and B. longum subsp. longum [31].…”
Section: Bifidobacterial Genomesmentioning
confidence: 99%
“…Stachyose and raffinose (sugars of the so-called raffinose family, which also includes verbascose) are present in a wide variety of plants (20), while the related sugar melibiose (though not a member of the raffinose family) is also found in many plants and is particularly abundant in soybean roots and stems (21). To metabolize such ␣-galacto-oligosaccharides, bifidobacteria require ␣-galactosidase enzyme activity, which has been identified and characterized in five bifidobacterial species or strains: Bifidobacterium bifidum JCM 1254 (22), Bifidobacterium adolescentis (23,24), Bifidobacterium bifidum NCIMB 41171 (25), Bifidobacterium breve 203 (26), and Bifidobacterium longum subsp. longum (27,28).…”
Section: Certain Bifidobacterial Strains Have Been Shown Previously Tmentioning
confidence: 99%